Bahiagrass (Paspalum notatum Flueggé): Overview and Pasture Management - Marcelo Wallau; Joao Vendramini; Jose Dubeux; Ann Blount (EDIS, 2019)
This 10-page document discusses bahiagrass forage cultivars, forage production, nutritive value, animal performance, planting, pasture renovation, management, and more. Written by Marcelo Wallau, Joao Vendramini, José Dubeux, and Ann Blount, and published by the UF/IFAS Agronomy Department, revised July 2019. https://edis.ifas.ufl.edu/ag342